A határon átnyúló együttműködések új lehetőségei és szerepük a hátrányos helyzetű kistérségek felzárkóztatásában - Horváth, Péter (Közép-Európai Közlemények, 2013)
Joining to the European Union creates the chance for the most disadvantageous sub-regions to start closing up in Hungary. Regions such as the ones along the Hungarian-Romanian and Hungarian-Ukrainian border fall into this category and their unfavourable situation can be illustrated by their peripherial location that is cumulative disadvantageous situation. The study introduces the advantages and disadvantages arising form being on the borderland through the inquiry of one particular sub-region focusing on three issues such as the opportunities created by: being on the borderland, the Romanian joining and the Schengen Agreement, the new forms of cooperation (The European Grouping of Territorial Cooperation). The results of the survey –which were done by the population –give a clear idea of the current situation. Based on my opinion and secondary fact-finding the aim of the study is to give objective conclusions and recommendations about the three issues mentioned above, which help us to determine the directions of intervention on a segmental part of the disadvantageous situation.